Evolution of somatic mutations in mammary tumors in transgenic mice is influenced by the inherited genotype - Podsypanina, Katrina (BioMed Central, 2004)
BACKGROUND: MMTV-Wnt1 transgenic mice develop mammary hyperplasia early in development, followed by the appearance of solitary mammary tumors with a high proportion of cells expressing early lineage markers and many myoepithelial cells. The occurrence of tumors is accelerated in experiments that activate FGF proto-oncogenes or remove the tumor suppressor genes Pten or P53, implying that secondary oncogenic events are required for progression from mammary hyperplasia to carcinoma. It is not known, however, which oncogenic pathways contribute to Wnt1-induced tumorigenesis – further experimental manipulation of these mice is needed. Secondary events also appear to be required for mammary tumorigenesis in MMTV-Neu transgenic mice because the transgene in the tumors usually contains an acquired mutation that activates the Neu protein-tyrosine kinase. METHODS: cDNA or DNA from the mammary glands and mammary tumors from MMTV-Wnt1, MMTV-Wnt1/p53(-/-), MMTV-Neu transgenic mice, and newly generated MMTV-Wnt1/MMTV-Neu bitransgenic mice, was sequenced to seek activating mutations in H-Ras, K-Ras, and N-Ras genes, or in the MMTV-Neu transgene. In addition, tumors from bitransgenic animals were examined to determine the cellular phenotype. RESULTS: We found activating mutations at codons 12, 13, and 61 of H-Ras in just over half of the mammary tumors in MMTV-Wnt1 transgenic mice, and we confirmed the high frequency of activating mutations of Neu in tumors in MMTV-Neu transgenic mice. Tumors appeared earlier in bitransgenic MMTV-Wnt1/MMTV-Neu mice, but no Ras or MMTV-Neu mutations were found in these tumors, which were phenotypically similar to those arising in MMTV-Wnt1 mice. In addition, no Ras mutations were found in the mammary tumors that arise in MMTV-Wnt1 transgenic mice lacking an intact P53 gene. CONCLUSIONS: Tumorigenic properties of cells undergoing functionally significant secondary mutations in H-Ras or the MMTV-Neu transgene allow selection of those cells in MMTV-Wnt1 and MMTV-Neu transgenic mice, respectively. Alternative sources of oncogenic potential, such as a second transgenic oncogene or deficiency of a tumor suppressor gene, can obviate the selective power of those secondary mutations. These observations are consistent with the notion that somatic evolution of mouse mammary tumors is influenced by the specific nature of the inherited cancer-promoting genotype.